Prenatal alcohol exposure results in brain region- and sex-specific changes in circHomer1 expression in adult mouse brain - Papageorgiou, Grigorios; Amoah, Stephen K.; Pierotti, Caroline; Otero, Madison; Eckel, Sophie; Coffey, Kacie; Allan, Andrea M.; Caldwell, Kevin K.; Mellios, Nikolaos (Frontiers in Neuroscience, 2023)
Circular RNAs (circRNAs) are a novel category of covalently-closed non-coding RNAs mainly derived from the back-splicing of exons or introns of protein-coding genes. In addition to their inherent high overall stability, circRNAs, have been shown to have strong functional effects on gene expression via a multitude of transcriptional and post-transcriptional mechanisms. Furthermore, circRNAs, appear to be particularly enriched in the brain and able to influence both prenatal development and postnatal brain function. However, little is known about the potential involvement of circRNAs in the long term influence of prenatal alcohol exposure (PAE) in the brain and their relevance for Fetal Alcohol Spectrum Disorders (FASD). Using circRNA-specific quantification, we have found that circHomer1, an activity-dependent circRNA derived from Homer protein homolog 1 (Homer1) and enriched in postnatal brain, is significantly down-regulated in the male frontal cortex and hippocampus of mice subjected to modest PAE. Our data further suggest that the expression of H19, an imprinted embryonic brain-enriched long non-coding RNA (lncRNA), is significantly up-regulated in the frontal cortex of male PAE mice. Furthermore, we show opposing changes in the developmental- and brain region specific- expression of circHomer1 and H19. Lastly, we show that knockdown of H19 results in robust increases in circHomer1 but not linear HOMER1 mRNA expression in human glioblastoma cell lines. Taken together, our work uncovers notable sex- and brain region-specific alterations in circRNA and lncRNA expression following PAE and introduces novel mechanistic insights with potential relevance to FASD.